Treatment-seeking behaviours of malaria patients versus non-malaria febrile patients along China-Myanmar border - Xu, Jian-Wei; Deng, Dao-Wei; Wei, Chun; Zhou, Xing-Wu; Li, Jian-Xiong (Malaria journal, 2023)
Background Appropriate malaria treatment-seeking behaviour (TSB) is critical for timely detecting malaria, prompt treatment, and prevention of onward transmission of the disease in a community. This study aimed to compare treatment-seeking behaviours between malaria patients and non-malaria febrile patients, and to analyse the factors associated with appropriate TSB along the China-Myanmar border. Methods A cross-sectional study was carried out to investigate the appropriate TSB of microscopy-confirmed malaria patients versus non-malaria febrile (NMF) patients. An unconditional logistic regression analysis (LRA) was used to identify factors associated with appropriate TSB. Results Among 223 malaria patients and 446 NMF patients, 129 (57.8%) of the malaria patients versus 163 (36.5%) of the NMF patients firstly sought treatment in health facilities without laboratory testing for malaria (P < 0.0001). A total of 85(38.1%) of the malaria patients versus 278 (62.3%) of the NMF patients had appropriate TSB, namely, seeking treatment in health facilities with laboratory testing for malaria within 48 h (P < 0.0001). Multivariate LRA identified that the malaria patients with Chinese nationality had less appropriate TSB compared to those with other nationalities (adjusted odds ratio [AOR]: 0.21, 95% confidence interval CI 0.07-0.68, P = 0.0097), and malaria patients residing in urban areas had more appropriate TSB compared to those living in rural areas (AOR: 2.16, 95%CI 1.06-4.39, P = 0.0337). Conclusions TSB was not appropriate in malaria patients. Chinese citizenship and rural residence were two independent factors associated with inappropriate malaria TSB. It is urgently necessary to improve appropriate malaria TSB through effective campaigns of information, education, and communication for malaria control in Myanmar and preventing reestablishment of malaria transmission in Yunnan, China. Keywords: Malaria, Treatment-seeking behaviour, Laboratory-based diagnosis, China-Myanmar border